Improved measurement for mothers, newborns and children in the era of the Sustainable Development Goals - Tanya Marchant; Jennifer Bryce; Cesar Victora; Allisyn C Moran; Mariam Claeson; Jennifer Requejo; Agbessi Amouzou; Neff Walker; Ties Boerma 7; John Grove 5 (Edinburgh University Global Health Society, 2016)
An urgent priority in maternal, newborn and child health is to accelerate the scale-up of cost-effective essential interventions, especially during labor, the immediate postnatal period and for the treatment of serious infectious diseases and acute malnutrition. Tracking intervention coverage is a key activity to support scale- up and in this paper we examine priorities in coverage measurement, distinguishing between essential interventions that can be measured now and those that require methodological development.